Recurrent duplications of the annexin A1 gene (ANXA1) in autism spectrum disorders - Correia, CT (2014)
BACKGROUND: Validating the potential pathogenicity of copy number variants (CNVs) identified in genome-wide studies of autism spectrum disorders (ASD) requires detailed assessment of case/control frequencies, inheritance patterns, clinical correlations, and functional impact. Here, we characterize a small recurrent duplication in the annexin A1 (ANXA1) gene, identified by the Autism Genome Project (AGP) study. METHODS: From the AGP CNV genomic screen in 2,147 ASD individuals, we selected for characterization an ANXA1 gene duplication that was absent in 4,964 population-based controls. We further screened the duplication in a follow-up sample including 1,496 patients and 410 controls, and evaluated clinical correlations and family segregation. Sequencing of exonic/downstream ANXA1 regions was performed in 490 ASD patients for identification of additional variants. RESULTS: The ANXA1 duplication, overlapping the last four exons and 3'UTR region, had an overall prevalence of 11/3,643 (0.30%) in unrelated ASD patients but was not identified in 5,374 controls. Duplication carriers presented no distinctive clinical phenotype. Family analysis showed neuropsychiatric deficits and ASD traits in multiple relatives carrying the duplication, suggestive of a complex genetic inheritance. Sequencing of exonic regions and the 3'UTR identified 11 novel changes, but no obvious variants with clinical significance. CONCLUSIONS: We provide multilevel evidence for a role of ANXA1 in ASD etiology. Given its important role as mediator of glucocorticoid function in a wide variety of brain processes, including neuroprotection, apoptosis, and control of the neuroendocrine system, the results add ANXA1 to the growing list of rare candidate genetic etiological factors for ASD.